1994
DOI: 10.1183/09031936.94.07030544
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and pathology of occupational asthma

Abstract: M Me ec ch ha an ni is sm ms s a an nd d p pa at th ho ol lo og gy y o of f o oc cc cu up pa at ti io on na al l a as st th hm ma a More than one mechanism may be operative in occupational asthma. Among the mechanisms proposed, immunological mechanisms and airway inflammation play an important role. There is evidence to confirm that T-lymphocyte activation and local accumulation in the bronchial wall of activated eosinophils occurs in asthma of diverse aetiology, i.e. immunoglobulin E (IgE)-mediated, occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 78 publications
1
50
0
Order By: Relevance
“…The present increase in subepithelial CD4+ T-cell density in nonsmokers with occupational asthma is comparable to what has previously been shown in ''traditional'' asthma [1,2], and illustrates the immunopathological similarity between occupational and nonoccupational asthma [13,14]. The lack of a similar increase in subepithelial CD4+ T-cell density in the smoking asthmatics was rather surprising, and apparently disagrees with the current concept of asthma immunopathology.…”
Section: Discussionmentioning
confidence: 40%
“…The present increase in subepithelial CD4+ T-cell density in nonsmokers with occupational asthma is comparable to what has previously been shown in ''traditional'' asthma [1,2], and illustrates the immunopathological similarity between occupational and nonoccupational asthma [13,14]. The lack of a similar increase in subepithelial CD4+ T-cell density in the smoking asthmatics was rather surprising, and apparently disagrees with the current concept of asthma immunopathology.…”
Section: Discussionmentioning
confidence: 40%
“…How exposure to isocyanates leads to isocyanate sensitization and asthma has been poorly defined. Studies to date, largely on TDI-and MDI-exposed patients, have found airway inflammation and suggest that isocyanate asthma is immunologically mediated predominantly through non-IgE mechanisms (1,2,7,15).…”
Section: Discussionmentioning
confidence: 99%
“…triggering asthma attacks) [36]. Among the mechanisms proposed in the pathogenesis of occupational asthma, the immunological one plays a key role [35].…”
Section: Mechanismmentioning
confidence: 99%
“…diisocyanates), textile workers (dyes) and users of plastics and epoxy resins (e.g. anhydrides) [35].…”
Section: Occupations At Riskmentioning
confidence: 99%
See 1 more Smart Citation